1999
DOI: 10.1017/s1367943099000335
|View full text |Cite
|
Sign up to set email alerts
|

Identification of evolutionary significant units in the Spanish wild goat, Capra pyrenaica (Mammalia, Artiodactyla)

Abstract: The Pyrenean population of Spanish wild goat (Capra pyrenaica pyrenaica) is nearly extinct.To find the most appropriate source of individuals for supplementing the Pyrenean population, we identified Evolutionary Significant Units (ESUs) among populations of the Capra pyrenaica species. We have examined sequence variability of portions of the mitochondrial DNA (mtDNA) control region and cytochrome b (cyt b) gene. Samples were from seven populations of Spanish wild goat distributed over the species' geographic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…The ibex population of the Natural Park of Sierra Nevada is very dense and larger than other populationsvalues ranged between 6.5 and 8.2 animals/km 2 until 2000 (Pé rez et al, 2002). Of the three metapopulations of C. pyrenaica included in this study, the Sierra Nevada metapopulation is the most genetically diverse (Manceau et al, 1999). This metapopulation maintains seven of the 10 haplotypes that characterize the Andalusian populations (Pé rez et al, 2002); the population from Malaga and Cadiz, which were included in the metapopulation Sierras de Má laga, only maintains two of the 10 haplotypes.…”
Section: Discussionmentioning
confidence: 95%
“…The ibex population of the Natural Park of Sierra Nevada is very dense and larger than other populationsvalues ranged between 6.5 and 8.2 animals/km 2 until 2000 (Pé rez et al, 2002). Of the three metapopulations of C. pyrenaica included in this study, the Sierra Nevada metapopulation is the most genetically diverse (Manceau et al, 1999). This metapopulation maintains seven of the 10 haplotypes that characterize the Andalusian populations (Pé rez et al, 2002); the population from Malaga and Cadiz, which were included in the metapopulation Sierras de Má laga, only maintains two of the 10 haplotypes.…”
Section: Discussionmentioning
confidence: 95%
“…Sequence analysis of the SI mitochondrial control and cytochrome b gene regions by Manceau et al (1999) demonstrated that the level of divergence between CPP and the other two extant SI subspecies was almost as high as the divergence between the SI and the Alpine ibex. We hypothesize that the recent extinction of the CPP subspecies might have involved a marked reduction in the allelic pool of the Capy-DRB1 and other MHC genes.…”
Section: Amills Et Almentioning
confidence: 99%
“…Nevertheless, the coexistence of a small population of Iberian wild goat and a large population of feral goats is a situation that should be monitored closely. The existence of this population, which originated from an unintentional escape, does not follow IUCN standards for re-introductions (2012), and belongs to a population that is genetically distant from the extinct Pyrenean wild goat (Manceau et al 1999). Thus, monitoring should continue, along with the study of this population's interactions with feral domestic goats; furthermore, its future must be decided as soon as possible, considering eradication or restocking .…”
Section: Discussionmentioning
confidence: 99%